The Effect Of Alloy Compositions On The Microstructure And Mechanical Properties Of Ceramic Matrix Composite Formed By Combustion Synthesis - Awallu, Yudha Rahman; , Wijianto, ST, M.Eng, Sc (2014)
The purpose of this research was to investigate the effect of alloy compositions on the microstructure and mechanical properties of product form by combustion synthesis. The research was done using powder materials such as C, Al, and TiO2. Using a reaction equation of 3TiO2 + (4+X) Al + 3C → 3TiC + 2Al2O3 + (X)Al, the powders was balanced to form a mixture which subsequently compacted to form a pellet. The composition of mixture was varied with excess of Al from 20%, 40%, 60%, 80%, to 100%. The ignition of combustion synthesis was done using arch flame. The results of the research showed that the ignition and combustion synthesis were succesfully observed in the reacted products. Using XRD and SEM observations, it was shown that Al and Al2O3 are the dominant phases of the synthesized products. Meanwhile, the microhardness test showed that increasing the content of Al has reduced the hardness. The higher hardness was observed in the product with highest content of Al2O3. This research has shown that the aluminium alloyed with Al2O3 formed by combustion synthesis has significant influence on the mechanical properties of product, with a substantial increase in its hardness.